(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRAK PNPM Mandiri community empowerment is a national program for poverty reduction as well independence society to grow and evolve in the direction.PNPM program can hape petrified society out of the problem of disability and poverty. Then in need of local government’s readiness to accept and implement the PNPM be continue actually be felt by society. Purpose of this study in accordance with the formulation of the problem is to dentermine how the implementation of comonity emporwerment program (PNPM) contriside in improving socie-ecomonic conditions of families in tobelo northern halmahera district. The research method uses destriptive reseacth/destribe and methods kualitatif.informan this study as many as 14 people in charge who know and accept the impact of the implementation of programsof PNPM tobelo. Data use is the primary data and data collection methods sekunder with interviews while research is research intrumen it selt. For data analysis done with together with data colletion, the data interpresti concluded later in the analysis,a description of the national program selfemprower ment(PNPM) rusal counties in the district tobelo halmahera utara. 2 Showcased in conclusion that the procces implementatin of PNPM mandiri in the district tobelo in 3 of 6 villages that can be said has been running, althogh there are still many who have not felt the impact of the program goverment can fix mistakes for a better direction, so that the need of peaple could be served for the better.